Odpowiedzi

2009-11-10T08:10:57+01:00
A=√2+3
b=2-3√2
a+b=√2+3+2-3√2=5-2√2
a*b=(√2+3)(2-3√2)=2√2-6+6-9√2=-6√2
a-b=√2+3-(2-3√2)opuszczamy nawias mieniamy znaki w nawiasia na przeciwne czyli mamy √2+3-2+3√2=4√2+1
a/b= √2+3/2-3√2całe równanie mnozymy przez √2i mamy
√2+3/-1=-√2-3
a² = (√2+3)²
a²= 2+6√2+9
a²= 11 + 6√2


(√2+3)³= √8 + 18+ 27√2+ 27= 45+ 27√2+ √8
Najlepsza Odpowiedź!
2009-11-10T08:15:13+01:00
A= √2 + 3
b= 2 - 3√2

a-b
√2+3-2+3√2= 4√2 +1

a+b
√2+3+2-3√2= -2√2 + 5

a×b
(√2+3)(2-3√2)= 2√2 - 3√4+6 - 9√2= -7√2

a÷b
(√2+3): (2-3√2) / ×(2+ 3√2)
(√2+3)(2+3√2) : (2-3√2)(2+3√2)
(2√2+6+6+9√2) : (4-18)
(11√2+12) : (-14)

b:a
(2 -3√2):(√2+3) / x (√2-3)
(2-3√2)(√2-3) : (√2+3)(√2-3)
(2√2-6 - 6+9√2) : (2-9)
(11√2 - 12) : (-7)

a= √2 + 3

a² = (√2+3)²
a²= 2+6√2+9
a²= 11 + 6√2


(√2+3)³= √8 + 18+ 27√2+ 27= 45+ 27√2+ √8
2009-11-10T13:09:01+01:00
A= √2 + 3
b= 2 - 3√2

a -b = √2 + 3 - (2 - 3√2) = √2 + 3 - 2 + 3√2 = 1 + 4√2

a + b = √2 + 3 + 2 - 3√2 = 5 - 2√2

a x b = (√2 + 3)(2 - 3√2) = 2√2 -6 + 6 -9√2 = -7√2

a : b = √2 + 3 / 2 - 3√2 = √2 + 3 x 1/ 2 - 3√2 = √2 + 3 / 2 - 3√2 =
(√2 + 3) (2 + 3√2) / (2 - 3√2) (2 + 3√2) = 2√2 + 6 + 6 + 3√2 /
4-18 = 12 + 5√2 / -4 = -3 + 5/4√2

a² = (√2 + 3)² = 2 + 6√2 + 9 = 11 + 6√2
a³ = (√2 + 3)³ = 2√2 + 18 + 27√2 + 27 = 45 + 29√2